THE REFLECTION OF CULTURE AND SPEECH BEHAVIORS OF CHINESE ANS RUSSIAN, THE USAGE OF REQUEST GRATITUDE, APPEAL, APOLOGY IN THE ADDRESSING - Xusainova, Zebo (Educational Research in Universal Sciences, 2023)
The article presents the key reasons for a comparative analysis of speech etiquette and its peculiarities in Russian and Chinese. One of the key reasons is the reflection, its role in speech etiquette, the features of culture, and national specificity of speech etiquette and behavior requires communicatively significant meaning. Apart from that, formulas of speech etiquette, its usage in a variety of situations associated with address, gratitude, apologies, and requests in Russian and Chinese analyzes the system of kinship terms in Chinese which is more detailed compared to the Russian language, indicates outcomes derived from the analysis of specific usage of the proper names in speech formulas.